1.6. Digital Archaeology in the Rural Andes: Problems and Prospects - (:unkn) unknown (My University, 2016)
This chapter explores the social context of digital archaeology conducted in a developing nation, with an emphasis on the archaeological project at Chavín de Huántar, in Peru. One might argue that the relevance, audience, and benefits of digital archaeology are primarily designed for and associated with wealthy universities, but this chapter attempts to demonstrate that digital archaeology is relevant to a broader public and community audience than just academics in the global north. Digital methods are able to be both relevant and beneficial to local communities. These communities, however, are not always naturally included stakeholders in these conversations, and this is an issue that must be acknowledged. This chapter addresses some of the problems in transitioning to a fully digital archaeology in the Andes and the means by which archaeology can assist in decolonizing our knowledge of the past.
Keywords: Chavín de Huántar; decolonizing practice; digital archaeology; heritage; inequality